Análise dos benefícios do edi para a competitividade logística das organizações - Carvalho, Glauco José de; Campos, Renato de [UNESP] (Universidade Tecnologica Federal do Parana (UTFPR), 2013)
The concept of EDI -Electronic Data Interchange is normally used to determine integration technologies between companies. Logistically, this implies in the integrationbetween enterprises in supply chain, involving the electronic transmission of data and thus reducing human intervention in the process, still favoring organizational performance. This study investigated the main benefits of EDI for organizational competitiveness and its possible impacton improving logistics performance of four companies comprising large national networks. Through multiple case studieswere able to identify common features that the use of EDI can favorer these companies. The results were significant and assume that the use of this tool can add value to logistics, primarily through streamlining processes, inventory optimization, cost reduction and performance improvement potential. Thus, the use of Electronic Data Interchange as a strategic tool for logistics proved, through this study, an efficient alternative for business improvement and good practice, able to leverage competitive advantages not only for individual companies, but also for the entire supply chain.

O conceito de EDI - Electronic Data Interchange é normalmente utilizado para determinar tecnologias de integração entre empresas. Em termos logísticos, isto implica em uma integração entre empresas na cadeia de suprimentos, envolvendo a transmissão eletrônica de dados e diminuindo, assim, a intervenção humana no processo, favorecendo ainda o desempenho organizacional. Este trabalho investigou os principais benefícios do EDI para a competitividade organizacional e seu possível impacto na melhoria do desempenho logístico de quatro empresas que integram grandes redes nacionais. Por meio do estudo de casos múltiplos foi possível identificar aspectos comuns que a utilização do EDI pode favorer a estas empresas. Os resultados foram significativos e pressupõem que a utilização desta ferramenta pode agregar valor à logística, principalmente por meio da agilização dos processos, otimização dos estoques, redução de custos e melhoria do desempenho potencial. Assim, o uso do Intercâmbio Eletrônico de Dados como uma ferramenta estratégica para fins logísticos se mostrou, por meio deste estudo, uma alternativa eficiente para melhoria dos negócios e uma boa prática, capaz de alavancar vantagens competitivas não somente para as empresas isoladas, mas também para toda a cadeia de suprimentos.
Analysis of the benefits of edi for logistics competitiveness of organisations
Keywords: Logistics; Strategy; Competitiveness; EDI; Logística; Estratégia; Competitividade; EDI